Основні засади та фактори державного регулювання економічної безпеки України - Лавренкова, І. М.; Lavrenkova, І (КНТУ, 2014)
У статті проведено дослідження основних засад державного регулювання економічної безпеки України, обґрунтовано необхідність визначення чіткого інструментарію для регулювання економічної безпеки, визначені найефективніші принципи та пріоритети державної політики, які можуть бути застосовані для подолання хиткого становища економіки країни. The research of the basic principles of state regulation of economic security in Ukraine was conducted in this paper. The necessity of definitions of an accurate tool for ensure of the economic security was founded. The most effective principles and priorities of the state policy that can be used to overcome the precarious position of the state economy were formulated in our research. Protection of vital interests of the state is a priority issue in the study of economic security of Ukraine. The state regulation is necessary for create and provide a secure space for economic activities of the country. State Department of Economic Security clearly intended to settle all problems to avoid the negative impact of external and internal factors on the economic system of Ukraine.
Basic Principles and Factors of State Regulation of Economic Security of Ukraine
Keywords: економічна безпека; державне регулювання; стратегічне управління; стратегія економічного розвитку; державна політика; economic security; government regulation; control; efficiency; state policy; principles